Iron deficiency anemia associated factors and early childhood caries in Qingdao - Shuaiqi Ji; Xiaohang Guan; Lei Ma; Pingping Huang; Hao Lin; Rui Han (BMC, 2022)
Abstract Background Iron deficiency anemia (IDA) has been shown to be related to early childhood caries (ECC). However, data on the relationship, if any, between IDA-associated factors and ECC remain scant. This study aimed to explore the interplay between IDA-associated factors and ECC. Methods This study randomly sampled a total of 1598 children in Qingdao city, and analyzed the severity of ECC using decayed-missing-filled teeth index, while the rate of caries was analyzed following the WHO recommendations. The correlation between IDA and ECC was analyzed by both the chi-square test and Mann-Whitney U test. In addition, we designed an electronic questionnaire and employed the disordered multi-classification logistic regression to interrogate the relationship between the IDA-associated factors and ECC. Results Children with IDA had higher rates and severe ECC than those without IDA (p < 0.001). Children who were breastfed until 2 years old had a higher risk of IDA and ECC, compared to those who were not {OR 3.453 (1.681-7.094)}. Compared with children who had no history of IDA at the age of 2 years or below, those with IDA history had a higher risk of IDA and ECC {OR 8.762 (3.648-21.041)}. In addition, children who had a maternal history of IDA at pregnancy were at a higher risk of IDA and ECC compared to those who had no IDA history at pregnancy {OR 4.913 (2.934-8.226)}. Our data showed that children from a family with an annual income lower than 50,000 Renminbi (RMB) had a higher risk of IDA and ECC compared to those with an annual family income higher than 200,000 RMB {OR 3.421 (1.505-7.775)}. On the other hand, compared with children taking iron supplements, children who did not were at a higher risk of ECC and IDA {OR 5.602 (1.858-16.896)}. Conclusion Factors such as low family income, history of IDA in children aged 2 years or younger, IDA history during pregnancy, children breastfed until 2 years old, and those not taking iron supplements were significantly associated with the occurrence of ECC and IDA.